Risk management : value at risk and beyond - Dempster, M. A. H. (Michael Alan Howarth), 1938- (Cambridge ; New York : Cambridge University Press, 2002)
This text examines the complex issues that concern the stability of the global financial system by presenting a mix of theory and practice. It should be essential reading for all involved in financial risk management.
Includes bibliographical references.
Keywords: Derivative securities; Risk management